THE COMPETITIVE ADVANTAGE OF SIDO MUNCUL: USING PESTLE, PORTER’S FIVE FORCES, AND SWOT MATRIX ANALYSIS - Ardi Kho; Jacob Donald Tan; Michael Prayogo Nugroho; Stefani Mutiara Kornelius; Sonnia Prayoga; Stephen Adi (Universitas Pelita Harapan, 2023)
Sido Muncul is a company engaged in herbal medicine, pharmaceutical, traditional medicine, health food and beverage, cosmetics, and herbal processing. It is continuously innovating its products and keeping an eye on market needs. Sido Muncul gains a place in the hearts of consumers and is one of its business strategies. In addition, Sido Muncul is also expanding into foreign markets to market and sell its products. This study uses the description of PESTLE analysis, Porter 5 Forces, and SWOT Matrix because it experiences significant challenges from competitors, regulations, the economy, internal companies, and changes in consumer behavior. Based on the PESTLE, Porter 5 Forces, and SWOT Matrix analysis, Sido appears to have strength in market growth and has unique products and competencies to survive in competition, gain profits and continue improving efficiency and product innovation. The company needs to improve: the younger generation does not use herbal products for health.